Dielectric properties of polypropylene blended with copolymers of varying ethylene contents - Kamarudin, Siti Noorhazirah; Lau, Kwan Yiew; Ahmad, Noor Azlinda; Azrin, Nur Azalia; Ching, Kuan Yong; Ghani, Ahmad Basri Abd; Arifin, Nur Amira Nor (Polymer engineering and science, 2024)
Polypropylene (PP) has recently been actively investigated as a potential power cable insulation substitute for crosslinked polyethylene (XLPE). This is mainly due to PP's higher thermal withstand capability over XLPE. Notably, PP has much higher stiffness than XLPE and therefore needs to be modified with tougher materials to reduce its overall stiffness while maintaining its desirable dielectric properties. To date, many investigations have been conducted on the mechanical and dielectric effects of PP blended with various copolymers. Nevertheless, systematic investigations on the dielectric effects of PP blended with ethylene‐based copolymers having different ethylene contents are less explored. The current work therefore reports on the impact of different ethylene contents of ethylene‐based copolymers on the breakdown performances of PP. The findings reveal that PP blended with a copolymer having a low ethylene content (68.7 wt%) results in at least 11% higher breakdown performance than PP containing a copolymer having a high ethylene content (77.0 wt%). Specifically, PP containing 10 wt% of copolymers having 68.7 wt% of ethylene content results in comparable breakdown performance to XLPE (325 kV mm−1). These results suggest that ethylene‐based copolymers with an appropriately low ethylene content can be blended with PP to achieve desirable breakdown properties. Highlights PP is blended with copolymers of varying amounts and ethylene contents. PP blended with low amounts of copolymers has good breakdown strength. PP blended with low ethylene level copolymers has favorable breakdown strength. PP blended with copolymers of low ethylene contents is desirable. The breakdown mechanisms are related with the structure and permittivity. Breakdown performance of PP/copolymer blends.